Resolving Authority Dualism Between National Sharia Arbitration Board and Sharia Courts Through Maslahah - Arminsyah; Indra Utama Tanjung; Siti Arifah Syam (As-Siyasi: Journal of Constitutional Law, 2026)
The development of the Sharia economy in Indonesia requires a dispute resolution mechanism that ensures legal certainty, justice, and effective law enforcement. However, the coexistence of National Sharia Arbitration Board (BASYARNAS)  and the Sharia Court has created a dualism of authority concerning jurisdiction, institutional legitimacy, and the enforcement of Sharia arbitration awards. This study aims to analyze the authority conflict between BASYARNAS and the Sharia Court and to formulate a harmonization model based on the principle of maslahah. Using a normative legal research method, the study employs statutory, conceptual, and philosophical approaches through the analysis of legislation, court decisions, and relevant legal doctrines. The findings reveal that the authority dualism originates from regulatory disharmony between arbitration law and religious court regulations, resulting in legal uncertainty and obstacles to the enforcement of Sharia arbitration awards. The study proposes a maslahah-oriented harmonization model that positions BASYARNAS as the institution responsible for resolving Sharia economic disputes through arbitration, while the Sharia Court functions as the supervisory, legalizing, and enforcing authority for arbitration awards. This model strengthens institutional coherence and legal certainty within the Sharia economic dispute resolution framework. The study contributes to the development of constitutional and Sharia economic law scholarship and provides recommendations for regulatory synchronization to establish an integrated, effective, and equitable dispute resolution system.